الممارسات المهنية لدى قائدات المدارس بمنطقة الباحة من وجهة نظر المعلمات - الغامدي، فاطمة علي حسن (جامعة القاهرة - فرع الخرطوم - كلية الآداب, 2020)
The study aimed at identifying the degree of achievement the professional standards of the school leaders in Al-baha region from female teachers point of view. The researcher used the descriptive approch. The study population consisted of (3784) teachers and their sample of (344) teachers. A questionnaire was used which consisting of (39) items to collect the data after verifying the validity and realiblty. The results showed that the degree of achievement of the professional standards of the leaders of schools in Al baha region was high with a mean of (4.13). The domains were ranked in descending order as follows: Values and Professional Systems with a mean of (4.47), educational support and development with a mean of (4.20), improving the learning environment with a mean of (4.19), supervisory role with amean of (4.11) at last planning domain with amean of (3.58).The results showed that there were no statistically significant differences at the level of (α≤0.05) according to the variable of experience. Also the results showed that there were statistically significant differences at the level of (α≤ 0.05) due to the variable of stage in favor of elementary level. The study recommended a number of recommendations, including: modernization and development of professional standards for school leaders so that school leaders can follow the latest developments in the world.
هدفت الدراسة إلى تعرف درجة توفر الممارسات المهنية لدى قائدات المدارس بمنطقة الباحة من وجهة نظر المعلمات. وقد استخدمت الباحثة المنهج الوصفي المسحي، واستبانة مكونة من (39) فقرة لجمع البيانات بعد التحقق من صدقها وثبا وتكون مجتمع الدراسة من (3784) معلمة، وعينتها من (344) معلمة. وأظهرت النتائج أن درجة توفر الممارسات المهنية لدى قائدات المدارس بمنطقة الباحة جاءت كبيرة، وبمتوسط حسابي بلغ (4.13)، وجاءت المجالات مرتبة تنازليا على النحو الآتي: مجال القيم والأنظمة المهنية، بمتوسط حسابي بلغ (4.47)، مجال الدعم والتطوير التربوي بمتوسط حسابي بلغ (4.20)، مجال تحسين بيئة التعليم، بمتوسط حسابي بلغ (4.19) مجال الدور الإشرافي بمتوسط حسابي بلغ (4.11)، مجال التخطيط، بمتوسط حسابي بلغ (3.58)، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (a≤0.05) تبعا لمتغير الخبرة، ووجود فروق ذات دلالة إحصائية عند مستوى الدلالة (a≤0.05) تبعا لمتغير المرحلة التعليمية لصالح المرحلة الابتدائية وأوصت الدراسة بعدد من التوصيات منها الاستمرار في تطوير الممارسات المهنية للقيادات المدرسية لمواكبة المستجدات العالمية، واختيار أفضل القيادات لتطوير الممارسات المهنية.
Keywords: الإدارة التعليمية -- الممارسات المهنية -- القيادات التربوية -- مديرو المدارس